2004
DOI: 10.1136/hrt.2003.025684
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity and cardiac function assessed by tissue Doppler imaging in chronic heart failure

Abstract: Objective: To examine the relation between longitudinal left ventricular function assessed by tissue Doppler imaging (TDi) and exercise capacity in heart failure. Subjects: 153 patients with chronic heart failure from left ventricular systolic dysfunction (ejection fraction , 45%) and 87 age and sex matched controls. Methods: Echocardiography was used to measure conventional indices of left ventricular systolic function. TDi was used to assess left and right ventricular longitudinal function by measuring mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 42 publications
4
33
0
1
Order By: Relevance
“…This analysis is further supported by the inverse correlation we found between LA enlargement and exercise capacity. Ejection fraction, relied on by clinicians, was of no help, since it was normal as an inclusion criterion, confirming previous evidence which showed no relationship with exercise capacity [22,23]. Detailed analysis of LV myocardial function can be assessed by different Doppler ultrasound techniques such as tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE).…”
Section: Data Interpretationmentioning
confidence: 90%
“…This analysis is further supported by the inverse correlation we found between LA enlargement and exercise capacity. Ejection fraction, relied on by clinicians, was of no help, since it was normal as an inclusion criterion, confirming previous evidence which showed no relationship with exercise capacity [22,23]. Detailed analysis of LV myocardial function can be assessed by different Doppler ultrasound techniques such as tissue Doppler imaging (TDI) and speckle tracking echocardiography (STE).…”
Section: Data Interpretationmentioning
confidence: 90%
“…In general, many studies have failed to show a significant link between exercise capacity (peak VO 2 ) and LVEF in patients with chronic heart failure, 42) and it has been reported that peak VO 2 is superior to LVEF as a prognostic predictor. However, in this study population, because averaged LVEF was about 60% and several patients with preserved LVEF were included, it seemed that LVEF was the strongest prognostic parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the role of the heart has been emphasized, but that different indices of LV dysfunction (and not just ejection fraction) need to be monitored, for example, indices of longitudinal LV function assessed by tissue Doppler imaging [8]. Furthermore, LV asynchrony, rather than uniform depression of systolic ventricular function, may play a key role in determining the maximum exercise tolerance by prolonging the total isovolumic period within the cardiac cycle [9].…”
Section: The Heartmentioning
confidence: 99%